2014
DOI: 10.1530/erc-13-0227
|View full text |Cite
|
Sign up to set email alerts
|

Diet-induced macrophage inhibitory cytokine 1 promotes prostate cancer progression

Abstract: Recent studies have indicated that a high-fat diet (HFD) plays an important role in prostate cancer (PCa) progression. Palmitic acid (PA) is one of the most abundant saturated free fatty acids (FAs) and is associated with carcinogenesis. In this study, we investigated the mechanism underlying the association of dietary fat, including PA, with PCa progression. In four PCa cell lines, in vitro PA administration stimulated the expression of macrophage inhibitory cytokine 1 (MIC1), which is a divergent member of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 38 publications
2
23
0
Order By: Relevance
“…Our current study is the first to illustrate the detrimental effects of a high energy or high fat diet (HED) on ovarian cancer progression. As in other tumor types [46-49], we found that HED promotes an aggressive growth pattern of ovarian tumor spread in the syngeneic ID8 tumor bearing mice. A high tumor burden was observed at most organ sites in HED mice (kidney, liver, spleen, peritoneum and bowel) along with a wider spread to the abdominal adipose tissue and lungs compared to the RD mice (Figs.…”
Section: Discussionsupporting
confidence: 80%
“…Our current study is the first to illustrate the detrimental effects of a high energy or high fat diet (HED) on ovarian cancer progression. As in other tumor types [46-49], we found that HED promotes an aggressive growth pattern of ovarian tumor spread in the syngeneic ID8 tumor bearing mice. A high tumor burden was observed at most organ sites in HED mice (kidney, liver, spleen, peritoneum and bowel) along with a wider spread to the abdominal adipose tissue and lungs compared to the RD mice (Figs.…”
Section: Discussionsupporting
confidence: 80%
“…To determine the relative contribution of the obesity-associated dysregulations of the endocrine metabolic milieu (alterations in the glucose/insulin metabolism and other systemic changes) in the pathologic association between HFD and prostate cancer and in the beneficial antitumoral effects of metformin, we used a mouse model with partial resistance to HFDinduced obesity (16)(17)(18) to be able to analyze the role of the intake of higher fat proportion in the diet (HFD-feeding) and metformin treatment in the progression of xenografted prostate cancer cells without the confounding effects of dysregulated endocrine metabolic conditions. As previously reported, this mouse model did not significantly gain body weight under HFD feeding compared with LFD animals (16-18), which was accompanied by similar body composition and glucose, insulin, and corticosterone levels, with the only observed alteration in leptin levels, which were elevated in HFD-fed mice.…”
Section: Discussionmentioning
confidence: 99%
“…To achieve these goals, we used a combination of different in vivo and in vitro approaches, including the use of a mouse model with partial resistance of HFD-induced obesity (16)(17)(18) to dissect out the role of HFD-feeding or LFD-feeding intake and metformin treatment in the development and progression of xenografted prostate cancer cells without the confounding effects of dysregulated endocrine metabolic conditions as well as, normal-like and/or prostate cancer cell lines to evaluate the in vitro effect of metformin in proliferation, migration, and/or prostate-specific antigen (PSA) secretion.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, several studies, including our own, have shown that a HFD and dietary components may alter gene expression, cellular activity, and induce other important changes in circulating biological factors related to PCa aggressiveness [5][6][7].…”
Section: Introductionmentioning
confidence: 95%
“…2b). Considering the accumulating evidence suggesting that palmitic acid (PA) stimulates MIC-1 expression in many types of cancer cells [7,25], we examined the role of increased FFAs on MIC-1 expression under a HFD condition. The mRNA expression level of MIC-1, but not GFRAL and TGF-beta, was signi cantly higher in PCa LNCaP, PC3, and DU145 cells after treatment with 0.125 mmol/l of PA, 0.25 mmol/l of oleic acid (OA), or 0.15 mmol/l of linoleic acid (LA) ( Figure S1 and Fig.…”
Section: Hfd and Exogenous Ffas Enhance The Expression And Secretion mentioning
confidence: 99%